Centrifuged casting of ductile iron using composite mold - Dikel, M; Üster, A; Kuskonmaz, N (WILEY-V C H VERLAG GMBH, 2005)
Ductile iron is widely used in the automotive and the related industries.The cast products are produced by using centrifugal casting, technique.They are high purity alloys and exhibit stability in the microstructure with similar microstructural appearance.When compared with other static casting methods, higher values in the tensile strength, % elongation, hardness, wear resistance and fatigue strength are obtained with centrifugal casting techniques. In this study, the cast products produced by the centrifugal casting technique using the composite mold consisting of ceramics and metal molds are inspected in order to observe the effect of centrifugal forces on the graphite particles present for discussing the changes observed in the graphite particle distribution, the hardness values and the microstructural formation in the direction from the outer to the center part of the cast product.
Keywords: centrifugal casting; ceramic mold; ductile iron; Materials Science